Can We Stop "Killer Algae" From Invading Florida? - Charles Jacoby; Linda Walters (EDIS)
SGEF-155, a 2-page illustrated fact sheet by Charles Jacoby and Linda Walters, describes the Mediterranean strain of Caulerpa taxifolia, or "killer algae", what it is, what it looks like, why it is invasive, and how people can help preventing an invasion of this noxious aquatic weed. Published by Florida Sea Grant, University of Florida, June 2004.